Structuring Liability in Performance-Based Copyright Infringement: A Legal Analysis of the Ari Bias and Agnes Mo Licensing Disputes - Alifa Nurdiannisa; Suherman (Lambung Mangkurat Law Journal, 2026)
Commercial music performances frequently involve the use of copyrighted works, yet creators in Indonesia continue to face losses arising from unlicensed song usage and unpaid royalties. The dispute between Ari Bias and Agnez Mo highlights a longstanding ambiguity in the Copyright Law particularly the absence of an explicit division of responsibility between singers and event organisers for obtaining licences and ensuring royalty payments. This study examines which party bears primary legal responsibility within the framework of Law No. 28 of 2014 on Copyright, using a normative juridical approach supported by literature-based data collection and qualitative descriptive analysis The study finds that although the Copyright Law does not expressly allocate responsibility, its formulation of “performers” encompasses both singers and event organisers. This interpretation aligns with the functional role each party plays in commercial performances: singers as those who communicate the work to the public, and organisers as entities that control the venue, derive economic benefit, and facilitate the commercial exploitation of the copyrighted work. Consequently, both parties share joint responsibility for obtaining licences and paying royalties. This interpretation is reinforced by the Supreme Court’s cassation ruling in the Ari Bias vs. Agnez Mo case, which identified error in persona due to the exclusion of the event organiser as a defendant. The decision underscores that responsibility in commercial song performances is inherently shared. These findings contribute to strengthening legal certainty and clarifying the obligations of singers, creators, and event organisers in Indonesia’s music industry, while demonstrating the need for more explicit regulatory guidance.